Enhancing Personal Data Security Awareness and Vigilance on Social Media Platforms (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
As the demand for personal information protection grows, vigilance and awareness regarding data and privacy security have become paramount concerns in social media platform usage. While studies indicate rising awareness levels, there remains a deficit in understanding the risks and effective methods for safeguarding personal data. Factors such as inadequate education, constrained privacy controls, and uncertainties surrounding platform privacy policies impede users' efforts to bolster personal data security. This activity aims to educate on the significance of digital privacy and foster vigilance and awareness of data and privacy security on social media platforms. The implementation of activity planning involved a national seminar combining material presentations and interactive discussions with cybersecurity practitioners from the Indonesia Honeynet Project (IHP) and the Indonesia Artificial Intelligence Society (IAIS), high school students, university students, teachers, lecturers, and the surrounding community. The success of this activity was marked by the successful dissemination of knowledge and understanding among the audience, both online and offline. This is expected to provide insights and mitigate risks associated with data and privacy security, promoting safer and more responsible platform usage